Tweeting television between innovation and normalization: How Lebanese television and audiences are making use of Twitter in political talk shows - Zebib, Chirinne (Žurnalistikos tyrimai, 2023)
Traditional media have progressively integrated newer media practices, with the constant emergence of new digital technologies, without abandoning their former ones. The adoption of Twitter by TV channels and by other social actors during political talk shows is a case in point. This article aims to assess whether the hybridization of TV talk shows and Twitter has innovated or normalized existing patterns of communication. In the former case, by enabling more interaction between different actors and space for audience deliberation, or in the latter case, by reproducing a traditional one-way communication and a centralized network of information that remains controlled and oriented by the elite (journalists and politicians). The incorporation of older and emergent media logic has an impact on the construction and distribution of political information as well as on the power relationships between journalists, politicians, and TV audiences. Besides allowing political talk shows to expand their flow of information, and to promote their news online, hybridized practices have not only altered the way citizens consume and engage with political information but also how they counter-frame traditional political media content by producing new ones. The research methodology consists of descriptive, content, and network analyses of tweets collected from three Lebanese local TV political talk show “Sarelwa2et” (MTV), “Btefro’ aa Watan” (Al Jadeed), and “Vision 2030” (LBCI) between February and March 2022. Results revealed that TV talk shows are making use of Twitter as a top-down transmitter of information and resorting poorly to its interactive potential. Some newer media practices of Twitter, such as @mention and replies are being applied but only to interact with politicians and journalists, failing to engage with a larger array of voices and thus, leading to an elite-centric discourse within the network. Also, tweets are mostly used to inform audiences and promote TV programs. In addition, network analyses of talk shows via hashtags demonstrated the central and not monopolized role of politicians and journalists as influencers, bridges, and quick spreaders of information. Finally, content analysis of dual screeners’ tweets (n=6000) indicated very little space in a Habermasian public sphere. The total of subjective opinions, irony, and attack/insult tweets are still higher than the total of the introduction of new issues and counter-frames tweets.